A brief review of land administration domain model and its temporal dimension - Babalola, Sunday Oyetayo (2015)
Land Administration Domain Model (LADM) is published by the International Organization for Standardization as ISO19152:2012. LADM stimulates the development of software application and accelerates the implementation of proper land management system in support of sustainable development. LADM covers essential information related to the components of land management including those over water and elements above and below the earth surface. LADM standard provides an abstract, conceptual model with three packages and one sub-package. LADM defined terminology for land administration that allows a shared description of different formal customary or informal tenures. The standard provides the basis for national and regional profiles and enables the combination of land management information from different sources in a coherent manner. In this paper, Land Administration Domain Model and basic knowledge were treated. The effort of the experts with the pioneers in the standardization and publication of LADM was discussed in order to set the foundation for the review. Some of the available works from 2006 when the standardization processes began were reviewed with more emphasis on the time (temporal) dimension of LADM. From available journal and papers, the authors agreed that there is need for addition of the time dimension with the existing 3D to manage the land use complexity in this recent time. We therefore concluded in this paper that, the design and development process for International Standard ISO 19152:2012 temporal schema will be adopted as a methodology to achieve the aim of this research.